The Influence of Intellectual Capital, Proportion of Independent Commissioners, Educational Background of the Board of Commissioners, Number of Audit Committee Meeting, and Corporate Social Responsibility Costs on Financial Performance - Nur Fatikasari, Maghfira; Laela Wijayati, Fitri (JAF (Journal of Accounting and Finance), 2025)
This study aims to analyze the factors that influence financial performance in companies within the energy sector. The population comprises all energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sampling technique used is purposive sampling, with the criteria being energy companies that remained listed on the IDX throughout 2020–2023. A total of 140 observations were obtained from 35 energy sector companies. The data were analyzed using panel data regression analysis. The findings reveal that, simultaneously, intellectual capital, the proportion of independent commissioners, the educational background of the board of commissioners, the frequency of audit committee meetings, CSR expenditures, and firm size all influence financial performance. However, when tested individually, only intellectual capital has a significant positive effect on financial performance. In contrast, the proportion of independent commissioners, the educational background of the board of commissioners, the frequency of audit committee meetings, CSR costs, and firm size do not have a significant impact on financial performance.